Konsep Pendidikan Menurut Syekh Taqiyuddin An-Nabhani dan Relevansinya dengan Perkembangan Pendidikan di Era Globalisasi - Yusuf Supriadi; Imam Tholkhah; Muhammad Jaenudin (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This thesis formulates the main issues, namely: how is the biography of Taqiyuddin An Nabhani and his popular works related to the formation of an Islamic personality, how is the basic concept of Taqiyuddin An Nabhani's thought, and how is the construction of Taqiyuddin An Nabhani's thought in Islamic education. The purpose of this study is to identify and describe his popular works related to the formation of Islamic personality, to identify, analyze and describe the basic concepts of Taqiyuddin An Nabhani's thought, and to identify, analyze and describe the construction of Taqiyuddin An Nabhani's thought in the concept of Islamic education. The research which is categorized in this qualitative type is a research on the thoughts of the characters in the past. Therefore, this study uses a historical approach in analyzing and photographing the data, ideas and thoughts of Taqiyuddin An-Nabhani about the concept of Islamic personality formation. Keywords: Taqiyuddin An-Nabhani, Islamic Personality, Construction of Islamic Education Thought.